DMFC at low air flow operation: study of parasitic hydrogen generation - Dohle, H.; Mergel, J.; Ghosh, P. C. (Electrochimica Acta, 2007)
In this paper, the effect of hydrogen generation in direct methanol fuel cells (DMFC) is described. Under certain operating conditions hydrogen generation occurs in DMFC causing an additional methanol consumption and a decrease of the cell voltage. For the present experiments a segmented cell with an active area of 244 cm 2 is used. The cell has 196 segments which are regularly distributed on the whole area. By this experimental setup hydrogen generation was found in regions with insufficient air supply. Hydrogen generation was analyzed by systematically applying different air flow rates and detecting the local current densities. The theory for hydrogen generation is confirmed by the results obtained from the segmented cell. A correlation between open circuit voltage (OCV), air flow rate and hydrogen generation was observed. Furthermore, half-cell measurements with different methanol concentrations were performed and used for analyzing the processes during hydrogen generation. The work clearly indicates the importance of sufficient cathode air supply for DMFC. Starved cathode areas not only do not contribute to the overall current generation but in addition reduce the power and efficiency by the parasitic generation of hydrogen. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: DMFC; Efficiency; electrolytic hydrogen evolution; oxygen depletion; side-effects